From Lens to the World: Documentary Video as a Catalyst for Promoting the Potential of Remote Villages - Nur Apriani Buluatie; Hardianto; Ade Harni; Muh. Faldi; Arnanda Mardatillah; Alya Andriani; Nurul Maghfirah Adil; Alya Amelia; Aisa; Nur Fadilah; Masita; Sartika Usman; Kardiman; Yusriandi Achmad (S1 Teknik Mesin Fakultas Teknik. Universitas Negeri Surabaya Gedung A6 Kampus UNESA Ketintang Surabaya 60231, 2025)
ABSTRACT This community service activity aims to introduce the potential of Kanna Utara Village, Basse Sangtempe Subdistrict, Luwu Regency, through a documentary video as a promotional medium based on the Asset-Based Community Development (ABCD) approach. The program was implemented from July 7 to August 20, 2025, involving the village government, community leaders, and residents as key partners. The process included identifying potential, formulating expectations, designing, producing videos, and reflecting on sustainability. The outcome of the activity was a 6-minute documentary video showcasing the natural, agricultural, and cultural potential of the village, which successfully raised public awareness of the importance of digital promotion. The program also formed a village media team as a sustainability effort. The use of documentary videos proved to be an effective catalyst for promoting the potential of remote villages and strengthening a positive image based on local assets. Keywords: Village promise; local potential; ABCD method